CYP96T1 of Narcissus sp. aff. pseudonarcissus Catalyzes Formation of the Para-Para' C-C Phenol Couple in the Amaryllidaceae Alkaloids - Kilgore, Matthew B.; Augustin, Megan M.; May, Gregory D.; Crow, John A.; Kutchan, Toni M. (Frontiers in Plant Science, 2016)
The Amaryllidaceae alkaloids are a family of amino acid derived alkaloids with many biological activities; examples include haemanthamine, haemanthidine, galanthamine, lycorine, and maritidine. Central to the biosynthesis of the majority of these alkaloids is a C-C phenol-coupling reaction that can have para-para’, para-ortho’, or ortho-para’ regiospecificity. Through comparative transcriptomics of Narcissus sp. aff. pseudonarcissus, Galanthus sp., and Galanthus elwesii we have identified a para-para’ C-C phenol coupling cytochrome P450, CYP96T1, capable of forming the products (10bR,4aS)-noroxomaritidine and (10bS,4aR)-noroxomaritidine from 4’-O-methylnorbelladine. CYP96T1 was also shown to catalyzed formation of the para-ortho’ phenol coupled product, N-demethylnarwedine, as less than 1 % of the total product. CYP96T1 co-expresses with the previously characterized norbelladine 4’-O-methyltransferase. The discovery of CYP96T1 is of special interest because it catalyzes the first major branch in Amaryllidaceae alkaloid biosynthesis. CYP96T1 is also the first phenol-coupling enzyme characterized from a monocot.